2018
DOI: 10.1530/erc-18-0067
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab inhibits pituitary tumor cell growth modulating the TGFB/SMAD2/3 pathway

Abstract: In pituitary adenomas, early recurrences and resistance to conventional pharmacotherapies are common, but the mechanisms involved are still not understood. The high expression of epidermal growth factor receptor 2 (HER2)/extracellular signal-regulated kinase (ERK1/2) signal observed in human pituitary adenomas, together with the low levels of the antimitogenic transforming growth factor beta receptor 2 (TBR2), encouraged us to evaluate the effect of the specific HER2 inhibition with trastuzumab on experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…No significant difference was highlighted for TGF-β RI [133]. The same conclusion was drawn by Petiti et al [134], who also demonstrated that when incubated with trastuzumab, PitNET cell proliferation was inhibited via an enhanced expression of Smad2 and Smad3. This suggests that the TGF-β pathway is far more complex than previously believed, including the EGFR/Erk pathway (which, when activated, reduces Smad2 and Smad3 phosphorylation).…”
Section: Transforming Growth Factor Receptorsupporting
confidence: 73%
“…No significant difference was highlighted for TGF-β RI [133]. The same conclusion was drawn by Petiti et al [134], who also demonstrated that when incubated with trastuzumab, PitNET cell proliferation was inhibited via an enhanced expression of Smad2 and Smad3. This suggests that the TGF-β pathway is far more complex than previously believed, including the EGFR/Erk pathway (which, when activated, reduces Smad2 and Smad3 phosphorylation).…”
Section: Transforming Growth Factor Receptorsupporting
confidence: 73%
“…Immunoprecipitation of HER2 in normal and transformed epithelial cells was coimmunoprecipitated with the cadherin‐catenin complex, revealing a HER2 and β‐catenin in association with the basal condition . The connection between HER2 and SMAD3 independent of TGF‐β receptor might be regulated through β‐catenin/Smad3 colocalization …”
Section: Discussionmentioning
confidence: 99%
“…TGF-β comprises a family of growth factors, which play crucial roles in development, fibrosis, and cancer progression ( Nüchel et al, 2018 ). TGF-β binding activates type II and then type I receptors, that in turn activate an increase of SMAD signals activation ( Petiti et al, 2018 ; Lähde et al, 2021 ). Studies have demonstrated that high cancer-associated fibroblast infiltrated gastric cancer is associated with immunosuppressive microenvironment regarding to TGF-β alterations ( Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%